2003
DOI: 10.1093/jn/133.5.1238
|View full text |Cite
|
Sign up to set email alerts
|

Soy Isoflavones Exert Antidiabetic and Hypolipidemic Effects through the PPAR Pathways in Obese Zucker Rats and Murine RAW 264.7 Cells

Abstract: The hypocholesterolemic and anti-atherosclerotic mechanism by which soy may exert a beneficial effect remains unclear. Peroxisome-proliferator activated receptors (PPAR) are promiscuous nuclear receptors that regulate the transcription of genes involved in lipid and glucose homeostasis and lipid metabolism within the cell. We hypothesize that the isoflavones improve lipid and glucose metabolism by acting as an antidiabetic PPAR agonist. Male and female obese Zucker rats (OZR) were used as a model of Type 2 dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
278
5
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 369 publications
(324 citation statements)
references
References 38 publications
29
278
5
5
Order By: Relevance
“…Activation of PPARα has been previously demonstrated in several other studies (10,11,12,22). Unexpectedly, however, these fractions in the present study did not induce PPARγ transcriptional activity.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Activation of PPARα has been previously demonstrated in several other studies (10,11,12,22). Unexpectedly, however, these fractions in the present study did not induce PPARγ transcriptional activity.…”
Section: Discussionsupporting
confidence: 62%
“…The well-established beneficial effects of dietary soy on lipid metabolism and insulin sensitivity have been recently attributed to the activation of PPARα and PPARγ, respectively, by soy isoflavones (1,8,10). However, little is known about the possibility that isoflavones activate PPARβ/ δ, which plays a critical role in the regulation of metabolic homeostasis, and also in cardiac lipid metabolism (15,16), fetal development (17), inhibition of human cancer cell line growth (18), protection against liver toxicity (19), modulation of inflammation (6,20), and improved skeletal muscle oxidative enzyme activity in obese patients with type 2 diabetes mellitus (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vedavanam et al suggested that soy isoflavones may be beneficial for diabetic subjects due to their estrogenic activity and their ability to prevent glucose-induced lipid peroxidation and because they inhibit intestinal glucose uptake by decreasing sodium-dependent glucose transporter, resulting in a reduction of postprandial hyperglycemia [42]. Mezei et al demonstrated that isoflavones improve lipid and glucose metabolism by acting as a PPAR agonist [43]. An isoflavone-containing soy extract doubled PPARdirected gene expression, and a similar induction was observed when the soy isoflavones genistein or daidzein were used to treat cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, genistein and daidzein, found in soybeans and processed soy protein, have been shown to bind to the peroxisome proliferator-activated receptors (PPAR), particularly to PPAR as well as PPAR and (Dang et al 2003;Mezei et al 2003), suggesting the potential value of isoflavones as a nutritional approach to modulate the action of insulin. PPARs belong to a family of transcription factors of which include three isoforms, PPAR , PPAR ( ) and PPAR .…”
Section: Beneficial Effect Of Soybean On the Metabolic Syndromementioning
confidence: 99%